If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -3 = -39 + 3m Reorder the terms: -3 + 9m = -39 + 3m Solving -3 + 9m = -39 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -3 + 9m + -3m = -39 + 3m + -3m Combine like terms: 9m + -3m = 6m -3 + 6m = -39 + 3m + -3m Combine like terms: 3m + -3m = 0 -3 + 6m = -39 + 0 -3 + 6m = -39 Add '3' to each side of the equation. -3 + 3 + 6m = -39 + 3 Combine like terms: -3 + 3 = 0 0 + 6m = -39 + 3 6m = -39 + 3 Combine like terms: -39 + 3 = -36 6m = -36 Divide each side by '6'. m = -6 Simplifying m = -6
| 6(x-1)+4=3(7x+1) | | 5(2t-3)+4t=30-t | | 4y-3=0+y | | 15x^2-34x+15= | | (-3)-(2)= | | 5p+3=4p+6 | | 20p-2p+4p=20p-6p | | -17x-20=14x+70 | | -4x-11x=-75 | | 2.5x+3=15-1.5x | | 2x+1=4x-15 | | 2x-7=x+6 | | 17-5x=9+3x | | 5x+9=2x+30 | | 2x^2-x+6=0 | | 4x^2-44x+96= | | 7x-1=4x-3 | | 4x+0.2=6.6 | | 5x+4-4x=12-29 | | n^2-n+4=0 | | 5x-11-4x=-5 | | p=4n-50 | | 6k^2+22k-8=0 | | (x+2)(x+5)=-2 | | 4w+12w-10=16w-10 | | (6+4)*2-7+9+18+(5+1*3)+5=688 | | 3(0.6+2n)-3.2=7.6 | | x(x-5)=x^2+3x+5 | | 4x+13x=102 | | x^4-9= | | (6+4)*2-7+9+18+(5+1*3)+5=x | | 2x^2=-9x |